Inhibition of Porcine Epidemic Diarrhea Virus by Cinchonine via Inducing Cellular Autophagy - Ren, Jingping; Zeng, Wei; Jiang, Changsheng; Li, Chang; Zhang, Chengjun; Cao, Hua; Li, Wentao; He, Qigai (Frontiers in Cellular and Infection Microbiology, 2022)
Porcine epidemic diarrhea virus (PEDV) could cause lethal diarrhea and dehydration in suckling piglets, which can adversely affect the development of the global swine industry. The lack of effective therapeutical and prophylactic treatment especially for PEDV variant strains underlines the importance of effective antiviral strategies, such as identification of novel antiviral agents. In the present study, the antiviral activity of cinchonine against PEDV was investigated in Vero CCL81 and LLC-PK1 cells at a non-cytotoxic concentration determined by Cell Counting Kit-8 assay in vitro. We found that cinchonine exhibited a significant suppression effect against PEDV infection and its inhibitory action was primarily focused on the early stage of PEDV replication. Moreover, we also observed that cinchonine could significantly induce autophagy by detecting the conversion of LC3-I to LC3-II by using western blot analysis. Cinchonine treatment could inhibit PEDV replication in a dose-dependent manner in Vero CCL81 cells, while this phenomenon disappeared when autophagy was attenuated by pre-treatment with autophagy inhibitor 3MA. Consequently, this study indicated that cinchonine can inhibit PEDV replication via inducing cellular autophagy and thus from the basis for successful antiviral strategies which potentially suggest the possibility of exploiting cinchonine as a novel antiviral agent.